PECULIAR FEATURES OF ENGLISH AND UZBEK SPEECH ETIQUETTE (Web of Teachers: Inderscience Research, 2024)
The article analyzes the use of Uzbek phrases in English. These expressions are mainly used in the cultural and social spheres